2022
DOI: 10.1111/tid.13792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 in hematopoietic stem cell transplant recipients: A systematic review and meta‐analysis

Abstract: Background: Hematopoietic stem cell transplant (HSCT) recipients are at increased risk of mortality and morbidity with coronavirus disease 2019 (COVID-19) due to severe immune dysfunction. Methods:A literature search was performed on PubMed, Cochrane, and Clinical trials.gov from the date of inception to 12/08/2021. We identified 19 original studies reporting data on COVID-19 in HSCT recipients after screening 292 articles.Data were extracted following preferred reporting items for systematic reviews and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
2
29
2
1
Order By: Relevance
“…That said, it is uncontested that COVID-19 disease severity and morbidity are increased in the HSCT population, relative to the population at large. A systematic review and meta-analysis that included 19 studies published from the outset of the pandemic through December 31, 2021 reported on outcomes from 2031 HCT recipients who had a median age of 57 years, a median time from transplant of 23 months for autologous recipients and 16 months for allogeneic recipients, and a median time from COVID-19 diagnosis of 28 days (range 0–262); a pooled analysis revealed an intensive care unit admission rate of 29% and a mortality rate of 19% [ 37 ]. There was a slightly higher, though not statistically significant, mortality rate among allogeneic HCT recipients compared with autologous recipients, 21% vs 17%, respectively.…”
Section: Morbidity and Mortality In Hsct Recipientsmentioning
confidence: 99%
“…That said, it is uncontested that COVID-19 disease severity and morbidity are increased in the HSCT population, relative to the population at large. A systematic review and meta-analysis that included 19 studies published from the outset of the pandemic through December 31, 2021 reported on outcomes from 2031 HCT recipients who had a median age of 57 years, a median time from transplant of 23 months for autologous recipients and 16 months for allogeneic recipients, and a median time from COVID-19 diagnosis of 28 days (range 0–262); a pooled analysis revealed an intensive care unit admission rate of 29% and a mortality rate of 19% [ 37 ]. There was a slightly higher, though not statistically significant, mortality rate among allogeneic HCT recipients compared with autologous recipients, 21% vs 17%, respectively.…”
Section: Morbidity and Mortality In Hsct Recipientsmentioning
confidence: 99%
“… 1 The initial death rates among patients with hematological malignancies were high. 2 , 3 , 4 Although vaccination was rapidly developed, immunosuppressed patients were excluded from the initial studies; questions regarding efficacy and tolerance in these populations are only now being addressed. Responses in patients with hematological malignancies are particularly poor among patients with chronic lymphocytic leukemia and myeloma and further weakened upon exposure to daratumumab and to B cell-depleting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this survey, there has only been a small amounts of published articles describing how to manage hematopoietic cell transplant during the SARS-CoV-2 pandemic ( 11 , 15 19 ). They reported that patients received HSCT are at increased risk of infection with SARS-CoV-2 and COVID-19 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%